2003
DOI: 10.1155/2003/913679
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Acute Hepatitis E Infection with Co‐Existent Glucose‐6‐Phosphate Dehydrogenase Deficiency

Abstract: Hepatitis E virus is one of the leading causes of acute viral hepatitis in India but usually manifests as a mild self-limiting illness. Viral hepatitis in the presence of glucose-6-phosphate dehydrogenase (G6PD) deficiency may be associated with complications such as severe anemia, hemolysis, renal failure, hepatic encephalopathy and even death. The incidence of G6PD deficiency in the general population of northern India is reported to be between 2.2% and 14%. Despite both hepatitis E infection and G6PD defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…G6PD deficiency reportedly affects 2.2–14% of the north Indian population, and co-existence of both illnesses, though rare, has been documented 2,3. Acute viral hepatitis and HEV per se can lead to mild hemolysis; however, cases of severe hemolysis with markedly raised bilirubin with acute kidney injury, as in our patient, are very rare 3,4. Our patient had severe intravascular hemolysis, as evidenced by the rapid fall in hemoglobin, marked elevation in mixed hyperbilirubinemia, hemoglobinuria, and markedly raised plasma LDH.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…G6PD deficiency reportedly affects 2.2–14% of the north Indian population, and co-existence of both illnesses, though rare, has been documented 2,3. Acute viral hepatitis and HEV per se can lead to mild hemolysis; however, cases of severe hemolysis with markedly raised bilirubin with acute kidney injury, as in our patient, are very rare 3,4. Our patient had severe intravascular hemolysis, as evidenced by the rapid fall in hemoglobin, marked elevation in mixed hyperbilirubinemia, hemoglobinuria, and markedly raised plasma LDH.…”
Section: Discussionmentioning
confidence: 53%
“…Abid et al3 were the first to describe this rare life-threatening association in a series of five cases, four of which experienced renal failure leading to a long, protracted course of illness. Occasional reports have also suggested that HEV can cause massive hemolysis and renal injury in patients with G6PD deficiency 4,5…”
Section: Discussionmentioning
confidence: 99%
“…A similar relationship exists between malaria and sickle-cell disease. This is because the cells infected with the Plasmodium parasite are cleared more rapidly by the spleen (Monga et al,2003). This phenomenon might give G6PDH deficiency carriers an evolutionary advantage by increasing their fi tness in malarial endemic environments.…”
Section: Introductionmentioning
confidence: 99%
“…8 Likewise, hepatitis D superinfection in a chronic HBSAg carrier with G6PD deficiency has been associated with acute hemoglobinuria. 9 Severe anemia without major blood loss is an unusual feature of hepatitis A infection.…”
mentioning
confidence: 99%
“…Despite acute hemoglobinuria, this patient did not develop acute renal failure, contrary to previous reports. 7,8 G6PD catalyses the initial step in the hexose monophosphate shunt, oxidizing glucose-6-phosphate to 6-phosphogluconolactone, and reducing NADP to NADPH. The hexose monophosphate shunt pathway of glucose metabolism is the only red cell source of NADPH.…”
mentioning
confidence: 99%